Modelling of microfluidics network using electric circuits - Zaidon, Nuradawiyah; Nordin, Anis Nurashikin; Ismail, Ahmad Faris (2015)
This paper presents microfluidic network analysis using electric circuit methods by modifying the length of the channel segments that represent hydraulic resistance. It is crucial to precisely predicts flow and pressure in the channel by an accurate estimation of the hydraulic resistance of each segment, as microfluidics network become more complex and challenging. Furthermore, manipulation of channel length and size can be applied to design concentration gradient that based on repeated splitting, mixing and recombination fluid flow process, thereby producing a desired concentration profile. By using Hagen- Poiseuille’s law-Ohm’s law analogy, a batch of simulation 3D- microfluidic geometries was done using FLUENT while PSpice was used to validate the correlations of flow rate to current and hydraulic resistance to electrical resistance. This is done by characterizing hydraulic resistance of microchannels with different length to make-controlled volumetric mixing ratios at each branch. Different velocity magnitude contours and pressure profiles obtained from the channel length combinations agree well this analogy.